Original Method to Predict and Monitor Carbon Deposition on Ni-Based Catalysts During Dry Reforming of Methane - Ahmed, Rawaz; Sasaki, Takehiko; Olea, Maria (Frontiers in Chemical Engineering, 2020)
Although catalytic dry reforming of methane has recently attracted considerable attention from both environmental and economical points of view, due to the simultaneous utilization of two greenhouses with a high environmental impact, CO2 and CH4, and to the production of syngas (CO and H2 mixtures), a building block used for the synthesis of valuable chemicals and synthetic fuels, it has not yet been commercialized. Low-cost Ni-based catalysts with high activity have been developed. However, due to their major drawbacks (such as carbon formation and Ni particles sintering at high temperatures, which is required by the endothermic reaction), their industrial applicability is limited. What is more, access to advanced characterization techniques is needed to monitor coke deposition and to assess the efficiency of the dry reforming process, access which can be challenging for small and on-site laboratories. The focus of this current study is on the development and testing of a simple carbon deposition prediction method, which is easily accessible, based on the comparison of the gas composition measured at the exit of the reactor with the theoretical one, and calculated based on the process thermodynamics. Trustworthy results, confirmed by SEM and TGA/DSC measurements, were obtained when the method was applied for the monometallic, Ni/SBA-15, prepared by wet impregnation, and bimetallic, Ni-Co/SBA-15, and Ni-La/SBA-15 samples, prepared by both impregnation and co-impregnation, with different metal loading. The dry reforming process was performed at four temperatures: 550, 600, 650, and 700°C.